Radiological, Clinical, and Histological Findings in the Treatment of Pilonidal Sinus with Phenol Injection - Tonguc Utku YILMAZ; Omer YAVUZ; Ahmet Oktay YIRMIBESOGLU; Hasan Tahsin SARISOY; Cigdem VURAL; Umay KIRAZ; Nihat Zafer UTKAN (Medeniyet Medical Journal)
Objective: Sacrococcygeal pilonidal disease is a chronic discharging wound that causes pain and loss of quality of life. Phenol application is an outpatient procedure with low complications and low recurrence rates. We evaluated the radiological, histological, and clinical results of phenol application. Methods: A total of 44 consecutive patients with sacrococcygeal pilonidal disease underwent phenol application in Kocaeli University Faculty of Medicine, General Surgery Clinic between December 2015 and March 2017. Demographics, complaints, symptom duration, and the number of sinuses were recorded. Patients were examined using ultrasonography (USG) before surgery and two months after surgery. Four patients who wanted rhomboid excision and Limberg flap procedure underwent preoperative local phenol application and were excluded from the study. The excised tissues were used for pathological evaluation. Results: Purulent discharge was the leading symptom. All of the patients had hair in the preoperative USG evaluation, whereas five patients had still hairs in the sinuses in the postoperative USG examination. Four of these cases had recurrences on a 2-month follow-up. After phenol application, a 10% volume decrease was observed. Pathological examination was performed in four cases with phenol application, and in pathological material, the sinuses looked sclerotic and fibrotic. Conclusions: Our study revealed that a single phenol application achieved 90% success. However, no significant difference was observed in the cavity volume after phenol injection.